Structural Equation Model for Effectiveness of Technical Managers in Information Technology Industry - Yogesh N Naik; Monika Bisht (International Journal of Supply Chain Management, 2014)
In age of technology, the effectiveness of technical manager is keenly sought towards organizational growth and competitive advantage. Technical managers require a special combination of knowledge about science and technology to acquire respect, knowledge about behaviour, and skills to lead. This research presents a unique point of view, backed by empirical data analysis on how five key competencies, other than technology know-how impacts overall effectiveness of technical managers in Information Technology IT industry. A structural equation model (SEM) mines complex interdependencies amongst competency clusters which yield managerial effectiveness directly or indirectly. The survey instruments were employed on 520 technical managers from various technology centric departments across 19 IT organizations. Statistical techniques used include exploratory factor analysis (EFA); confirmatory factor analysis (CFA) and structural equation modelling (SEM). The role of project management, emotional intelligence (EI), domain knowledge, ethical values and business skills besides technical acumen is presented. Research findings are expected to help organizations in selection and development of technical managerial talent, and individuals towards self realization and self development.